2011
DOI: 10.3141/2264-12
|View full text |Cite
|
Sign up to set email alerts
|

Can Walking Behavior be Predicted?: Analysis of Calibration and Fit of Pedestrian Models

Abstract: Several models for simulation of pedestrian movement have been proposed in recent decades. These models are primarily used in the planning and evaluation of large pedestrian infrastructures, such as transportation hubs, with a focus to increase comfort and safety for pedestrians. Although the number of proposed simulation models is increasing at a fast pace, not much is known about the properties of calibration procedures or the transferability of the models estimated in one setting to other settings. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Model C: The third model is an implementation of Rudloff et al (2011) in which the repulsive force is split into one force directed in the opposite of the walking direction, i.e. the deceleration force, and another one perpendicular to it, i.e.…”
Section: Pedestrian Simulation Model Descriptionmentioning
confidence: 99%
“…Model C: The third model is an implementation of Rudloff et al (2011) in which the repulsive force is split into one force directed in the opposite of the walking direction, i.e. the deceleration force, and another one perpendicular to it, i.e.…”
Section: Pedestrian Simulation Model Descriptionmentioning
confidence: 99%
“…In order to model the way by which moving agents arrive in attractive areas, it is considered a parametric function that describes their velocities depending on the distance r to a center of force. The proposed model is based on a top speed from which the agent continuously experiments a deceleration according to a function inspired by the repulsive terms offered by [22,25] and the deceleration factor described on [26].…”
Section: Near Range Of Interactionmentioning
confidence: 99%
“…The methodology proposed by the authors is based on social force models, a concept originally introduced by [23]. In a recent work, Seer et al [24] extend the work of Helbing by using three different shapes of social forces models, namely radial [22], elliptical [25] and a split version of forces [26]. The work of Seer is evaluated on real pedestrian trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some researchers chose to remove the friction effect among pedestrians to describe pedestrian movement in normal conditions. 25,26 Considering the problems in the original SFM, this research aims to give detailed description of the mechanism of obstacle-avoiding behavior in normal conditions. It is often observed that some obstacles obstruct the movement of pedestrian flows in real walking facilities.…”
Section: Introductionmentioning
confidence: 99%